2015
DOI: 10.1097/brs.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability of Low- Versus High-Field Magnetic Resonance Imaging for Lumbar Degenerative Disease

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The diagnostic capability of low-field MRI (0.25 T) has been found comparable to that of high-field MRI (1.5 T and 3.0 T) with respect to degenerative findings of the lumbar spine, and it is not expected that the field strength had an influence on the results of the present study [48].…”
Section: Limitationssupporting
confidence: 72%
“…The diagnostic capability of low-field MRI (0.25 T) has been found comparable to that of high-field MRI (1.5 T and 3.0 T) with respect to degenerative findings of the lumbar spine, and it is not expected that the field strength had an influence on the results of the present study [48].…”
Section: Limitationssupporting
confidence: 72%
“…Therefore, there has been an increasing emphasis of late on the further development of low-field MRI systems (0.25-0.6 T) that are less expensive, with lower running costs, and low siting requirements, yet still produce images of comparable diagnostic capability for most clinical MRI studies that do not require ultra-high resolution. 28,29 The new open-bore configuration of low-field MRI systems can, depending on the particular machine design, allow for intervention MR guidance and scanning in various body positions including upright weight-bearing postures.…”
Section: Upright Weight-bearing Mri Systemsmentioning
confidence: 99%
“…8). 29 However, differences in reliability of the evaluation of tissue properties have been found between low-field and high-field MRI. The overall prevalence of disk degeneration graded by Pfirrmann's grading scale across MRI field strengths (0.25 T versus 3 T) was reported.…”
Section: Mri Findings On Low-field Versus High-field Mr Systemsmentioning
confidence: 99%
“…Using a i.e., a tilting low-field magnet of 0.25 T, supine and upright WB-MRI of the knee, spine and foot can be performed with potential added diagnostic value in selected pathologies 37,38 . Supine imaging of the spine in the WB-MRI system has also shown to have equal diagnostic potential in degenerative spine disease compared to high-field MRI examinations 39 . One study of KOA patients found that medial meniscal extrusion was significantly higher in WB-MRI compared to supine, and with a better correlation with KLG on CR and WORMS scores 40 .…”
Section: Diagnosismentioning
confidence: 99%